Pengembangan Objek Wisata Pantai Roto Di Desa Labuan Induk Kecamatan Labuan Kabupaten Donggala - Fitra, Fitra Lestari; Hattab, Syahruddin; Astuti, Agusta Sri (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the process of developing an environmentallybased roto beach tourist attraction in Labuan sub-district, donggala district by using George R. Terry's theory which includes aspects of planning, organizing, implementing, supervising. This research type is descriptive and the basis of research is qualitative. Data collection used is Observation, Interview, and Documentation. Data analysis techniques are carried out through the stages of data reduction, data presentation, and conclusion drawing/verification. The results of this study show that the development efforts of Roto Beach have shown positive steps in considering sustainability, especially through the preparation of village regulations related to development and greening and the creation of a master plan. However, the constraints faced are limited financial resources. In the organizing aspect, there is an organizational structure that involves the local community through the formation of Tourism Awareness Groups (Pokdarwis) and environmental care groups, although further development is still needed in the economic aspect with the formation of tourism business groups. At the implementation stage, there is success in mobilizing local community participation in socio-cultural activities, although there are still challenges in economic recovery after the 2018 natural disaster and environmental awareness. Supervision of all aspects of development still requires improvement, particularly in maintaining a balance between tourism development and preservation of local values, waste management and beach cleanliness, and fair and sustainable distribution of economic benefits.